Beta-Blockers for Primary Prevention of Anthracycline-Induced Cardiac Toxicity: An Updated Meta-Analysis of Randomized Clinical Trials. (29th December 2022) - Attar, Armin; Behnagh, Arman Karimi; Hosseini, Mehrasa; Amanollahi, Foad; Shafiekhani, Paria; Kabir, Ali
Abstract : Aim . Cardiotoxicity is a well-recognized complication of chemotherapy with Anthracyclines. However, results from trials evaluating beta-blockers for prevention are controversial. Therefore, we performed a meta-analysis to find whether prophylactic administration of beta-blockers can help prevent Anthracyclines-induced cardiotoxicity. Methods . We assessed randomized trials and observational studies where a prophylactic intervention was compared with a control arm in patients with a normal left ventricular ejection fraction (LVEF) receiving Anthracyclines. The primary outcome was EF reduction. The secondary outcome was the development of Cancer Therapeutics–Related Cardiac Dysfunction (CTRCD), defined as a decrease in the LVEF of >10% to a value of <53%. Results . We included 17 trials comprising 1291 patients (671 patients in the intervention arm and 620 in the control arm). Carvedilol was administered in eight studies, and others used bisoprolol, metoprolol, or nebivolol. Compared with baseline, LVEF reduced in both intervention and control groups after chemotherapy (MD = − 1.93 %, 95% CI: -2.94, -0.92, p = 0.001, I 2 = 72.1 % vs. MD = − 4.78 %, 95% CI: -6.51, -3.04, p = 0.001, I 2 = 91.6 %, respectively). LVEF was less reduced among the beta-blocker receivers (MD = 3.44 %, 95% CI: 1.41–5.46, p = 0.001, I 2 = 94.0 % ). Among the eight studies reporting the incidence of CTRCD, 45 out of 370 participants in the intervention arm and 54 out of 341 in the control arm were reported to experience this complication (RR = 0.76 ; 95% CI: 0.53, 1.09; I 2 = 24.4 % ; p = 0.235 ). Conclusion . Treatment with beta-blockers prevents dilatation of the left ventricle, development of diastolic dysfunction, and reduction of LVEF. However, these hemodynamic effects do not translate into a significant reduction in CTRCD incidence and prevention of hospitalization for heart failure or cardiac death.